QA09

#$&*

course MTH 279

3:01 2/25

q_a_09*********************************************

Question:

`q001.  Consider the equation y '' + 4 y ' - 5 y = 0.  Substitute y = e^(r t) and solve for r.

****

#$&*

You should have obtained two values of r.  For the moment call them r_1 and r_2.

Show that the following functions solve the above differential equation, for your values of r:

y = A e^(r_1 * t), where A can be any constant

****

#$&*

y = B e^(r_2 * t), where B can be any constant

****

#$&*

y = A e^(r_1 * t) + B e^(r_2 * t), where A and B can be any constants.

****

#$&*

If we want a solution with the conditions y(0) = 1 and y ' (0) = -1, can we adjust the constants A and B so that y = A e^(r_1 * t) + B e^(r_2 * t) is a solution?

****

#$&*

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

r_1 = 1

r_2 = -5

y_1 = Ae^1t

y_1'= y_1''= Ae^t

Ae^t+ 4Ae^t-5Ae^t = 0

Clearly:

1+4-5= 0

y_2= Be^-5t

y_2'= -5Be^-5t

y_2''= 25Be^-5t

25Be^-5t + 4(-5Be^-5t)-5(Be^-5t)

Again:

25-20-5= 0

Yes this can be done:

y(0)=1 --> A+B =0 --> A=-B

@& y(0) = 1 implies that A + B = 1, not 0.*@

y'(0)=-1 --> A-5B= -1 --> B= 1/6 --> A=-1/6

y = 1/6e^-5t - 1/6e^t

y'= -5/6e^-5t - 1/6 e^t

y''=25/6e^-5t - 1/6 e^t

(25/6e^-5t - 1/6 e^t) + 4(-5/6e^-5t - 1/6 e^t) - 5(1/6e^-5t - 1/6e^t) = 0

For one:

25/6 - 20/6 -5/6 = 0

for the other:

-1/6-4/6+5/6 = 0

@& The two simultaneous equations

A + B = 1

A - 5 B = -1

are easily solved. We obtain

A = 2/3, B = 1/3

so our the solution satisfying the initial conditions y(0) = 1, y ' (0) = -1 is

y = 2/3 e^t + 1/3 e^(-5 t).

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Self-critique:

------------------------------------------------

Self-critique Rating:

 

*********************************************

Question:

`q002.  Suppose f(t) = e^(2 t) and g(t) = e^(-3 t). 

Show that the determinant of the 2 x 2 matrix [ f, g ; f ', g ' ] (that is the matrix with first row f  g and second row f '  g ' ) is not identically zero.

****

#$&*

Suppose f(t) = t^2 and g(t) = t^3.

Show that the determinant of the 2 x 2 matrix [ f, g; f ', g ' ] is not identically zero.

****

#$&*

Show that if f is a constant multiple of g, then the determinant of the 2 x 2 matrix [ f, g; f ', g ' ] is identically zero.

****

#$&*

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

det [[e^2t, e^-3t][2e^2t, -3e^-3t]]= (e^2t * -3e^-3t) - (e^-3t * 2e^2t) = -2e^-t - 2e^-t = -4e^-t

det [[t^2, t^3][2t, 3t^2]] = 3t^2*t^2 - 2t*t^3 = 3t^4- 2t^4= t^4

f= C*g --> det [[f, g][f', g']] ---> det [[Cg, g][Cg', g']] = Cg*g' - Cg'*g = 0 this is clearly holds.

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Self-critique:

------------------------------------------------

Self-critique Rating:

 

*********************************************

Question:

`q003.  Recall that the span of two vectors v_1 and v_2 is the set of all their possible linear combinations v = a_1 v_1 + a_2 v_2, where a_1 and a_2 are scalar quantities.

Recall also that a set of vectors is linearly independent if there is no nontrivial linear combination of those vectors which is equal to zero, and that this condition is equivalent to saying that none of the vectors can be expressed as a linear combination of the others.

Functions can be regarded as vectors, with the scalars being the real numbers.  Two functions are said to be linearly independent if neither is a constant multiple of the other.

If the functions are f and g, then this condition is equivalent to saying that the determinant of [ f, g; f ', g ' ] is not identically zero.

In this case the set of linear combinations A f + B g is said to span a function space of two dimensions.

Show that the two functions f(t) = sin(t) and g(t) = cos(t) are linearly independent.

****

#$&*

Show that the function 2 sin(t) + 4 cos(t) is in the span of the set {f, g}.

****

#$&*

Show that the function t sin(t) - 2 cos(t) is not in the span of the set {f, g}.

****

#$&*

Show that any function in the set {e^t, e^(-t) } is linearly independent.

****

#$&*

Show that any function in the span of the set {e^t, e^(-t)} is a solution of the differential equation y '' - y = 0.

****

#$&*

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

det [[sin t, cos t][cos t, -sin t]] = -sin^2 t - cos^2 t ≠ 0

a_1 f + a_2 g--> 2 sin t + 4 cos t where a_1 = 2 and a_2 = 4

Here a_1 = t which is not a constant so this is not a constant multiple.

I'm not sure about what this is asking. The set only has two functions that are obviously LinInd and any {Ae^t, Be^-t }

@& {Ae^t, Be^-t } is only linearly independent if A and B are both nonzero.

In that -2 A B is nonzero so the determinant is nonzero.*@

combos are also LinInd as shown below.

det [[Ae^t, Be^-t][Ae^t, -Be^-t]] = Ae^t*-Be^-t - Ae^t*Be^-t = -2AB

y = Ae^t+Be^-t

y''= Ae^t+Be^-t

(Ae^t+Be^-t)-(Ae^t+Be^-t) = 0

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Self-critique:

------------------------------------------------

Self-critique Rating:

`q004.  e^(i * theta) = cos(theta) + i sin(theta).  This is easily seen by forming the Taylor expansion of e^x, sin(x) and cos(x) and substituting x = i * theta in the first series.  The equation e^(i * theta) = cos(theta) + i sin(theta) is called Euler's Identity.

Do this.

Whether or not you were successful in the preceding, use the laws of exponents to write the product e^(i * alpha) * e^(i * beta) as an expression with a single base and a single exponent.

****

#$&*

Use Euler's Identity to write this expression in terms of sines and cosines.

****

#$&*

Use Euler's Identity to write e^(i * alpha) and e^(i * beta) in terms of the sine and cosine function.

****

#$&*

Write out the product e^(i * alpha) * e^(i * beta) in terms of sines and cosines and simplify.

****

#$&*

Look at what you've done and see if you haven't derived the formulas for sin( alpha + beta) and cos(alpha + beta).

****

#$&*

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I can't seem to quite understand about how to setup the Taylor expansion with the i*theta substitution.

e^(i*alpha)*e^(i*beta) = e^(i*alpha+i*beta) = e^(i(alpha+beta))

e^(i(alpha+beta)) = cos (alpha+beta) + i sin (alpha+beta)

e^(i*alpha) = cos (alpha) + i sin(alpha)

e^(i*beta) = cos (beta) + i sin (beta)

e^(i*alpha)*e^(i*beta)= (cos (alpha) + i sin(alpha))*(cos (beta) + i sin (beta)) = (cos(alpha)cos(beta))+ (cos(alpha)i sin (beta)) + i sin(alpha)cos(beta) + i^2 sin(alpha)sin(beta)

[cos(alpha)cos(beta) - sin(alpha)sin(beta)] + [i(sin(alpha)cos(beta)+cos(alpha)sin(beta))]

This lefthand expression is for cos (alpha+beta) and the imaginary is for sin(alpha+beta)

@& The Taylor expansion for e^x is 1 + x + x^2 / 2 ! + x^3 / 3 ! + x^4 / 4 ! + ...

The Taylor expansion for sin(x) is x - x^3 / 3 ! + x^5 / 5 ! + ...

The Taylor expansion for cos(x) is 1 - x^2 / 2 ! + x^4 / 4 ! + ...

Substituting i * theta for x in the Taylor expansion of e^x we get

e^(i * theta) = 1 + (i * theta) + (i * theta)^2 / 2 ! + (i * theta)^3 / 3 ! + (i * theta)^4 / 4 ! + ...

= 1 + (i * theta) - theta^2 / 2 ! - i * theta ^3 / 3 ! + theta^4 / 4 ! + ...

= ( 1 - theta^2 / 2 ! + theta^4 / 4 ! + ... ) 1 + i * ( theta - theta ^3 / 3 ! ... )

= cos(theta) + i sin(theta).

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Self-critique:

------------------------------------------------

Self-critique Rating:

 

*********************************************

Question:

`q005.  Show that e^((i + 2) * t) and e^( (2 - i) * t) are linearly independent.

****

#$&*

If c_1 = a_1 + i * b_1 and c_2 = a_2 + i * b_2, then what is the general form of c_1 e^( (i + 2) * t) + c_2 e^( (2 - i) * t), in terms of sines and cosines?  You get something pretty messy, so simplify it as much as you can.

****

#$&*

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

det [[e^((i+2)t), e^((2-i)t)][(i+2)e^(i+2)t, (2-i)e^(2-i)t]] =

(e^((i+2)t)*(2-i)e^(2-i)t) - (e^((2-i)t)(i+2)*e^((i+2)t) =

(2-i)e^4t - (i+2)e^4t =

(4-2i)e^4t =

4e^4t - i*2e^4t

@& I got messed up the first time I did this.

The correct solution:

The Wronskian is

W(t) = [ e^( (i + 2) * t ) , e^( (2 - i) * t ) ; e^( (i + 2) * t ) ' , e^( (2 - i) * t ) ' ]

= [ e^( (i + 2) * t ) , e^( (2 - i) * t ) ; (i + 2)

e^( (i + 2) * t ) , (2 - i) e^( (2 - i) * t ) ]

= (2 - i) e^((i + 2 + 2 - i) t) - (i + 2) e^((i * 2 - 2 - i) t )

= (2 - i - (i + 2) e^(4 t)

= - 2 i e^(4 t)

which is never zero. So the functions are linearly independent.

*@

@& Also, take a good look at the following:

c_1 e^( (i + 2) * t) + c_2 e^( (2 - i) * t)

= e^(2 t) * (c_1 e^(i * theta) + c_2 e^(- i * theta) )

= e^2 ( (a_1 + b_1 i) * (cos(theta) + i sin(theta) ) + (a_2 + b_2 i) * (cos(theta) - i sin(theta) ) )

= e^2 ( a_1 cos(theta) - b_1 sin(theta) + i ( a_1 sin(theta) + b_1 cos(theta) )

+ a_2 cos(theta) + b_2 sin(theta) + i ( -a_2 sin(theta) - b_2 cos(theta) ) )

= e^2 ( (a_1 + i b_1) cos(theta) + (-b_1 + i a_1) sin(theta) + (a_2 + i b_2) cos(theta) + (-b_2 - i a_2) sin(theta) )

= e^2 ( (a_1 cos(theta) - b_1 sin(theta) + a_2 cos(theta) + b_2 sin(theta) ) + i * (b_1 cos(theta) + a_1 sin(theta) + b_2 cos(theta) - a_2 sin(theta) ) )

= e^2 ( (a_1 + a_2) cos(theta) + (-b_1 + b_2) sin(theta) + i ( (b_1 + b_2) cos(theta) + (a_1 - a_2) sin(theta) ) ).

Now the equations

a_1 + a_2 = A

-b_1 + b_2 = B

b_1 + b_2 = C

a_1 - b_2 = D

can be solved for a_1, a_2, a_3 and a_4 in terms of A, B, C and D (to prove this write this system down as a matrix product and take the determinant of the coefficient matrix; the result will be nonzero so you know the matrix can be inverted and the system solved; alternative you can row-reduce the matrix to the identity and prove the same; the matrix is [ 1, 1, 0, 0; 0, 0, -1, 0; 0, 0, 1, 1; 1, 0, 0, -1]).

Thus you can write the last step in the form

e^2 ( A cos(theta) + B sin(theta) + i ( C cos(theta) + D sin(theta) ) ),

where now A, B, C and D are arbitrary constants.

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

@& Looks good. Check my notes and see if you agree.*@